Melatonin stabilizes atherosclerotic plaques: an association that should be clinically exploited - Reiter, Russel J.; Sharma, Ramaswamy; Romero, Alejandro; Simko, Fedor; Dominguez-Rodriguez, Alberto; Cardinali, Daniel P. (Frontiers in Medicine, 2024)
Atherosclerosis is the underlying factor in the premature death of millions of humans annually. The cause of death is often a result of the rupture of an atherosclerotic plaque followed by the discharge of the associated molecular debris into the vessel lumen which occludes the artery leading to ischemia of downstream tissue and to morbidity or mortality of the individual. This is most serious when it occurs in the heart (heart attack) or brain (stroke). Atherosclerotic plaques are classified as either soft, rupture-prone, or hard, rupture resistant. Melatonin, the production of which diminishes with age, has major actions in converting soft to hard plaques. Experimentally, melatonin reduces the ingrowth of capillaries from the tunica media into the plaque relieving pressure on the plaque, reducing intraplaque hemorrhage and limiting the size of the necrotic core. Moreover, melatonin promotes the formation of collagen by invading vascular smooth muscle cells which strengthen the plaque crown making it resistant to rupture. Melatonin is also a powerful antioxidant and anti-inflammatory agent such that is reduces oxidative damage to tissues associated with the plaque and limits inflammation both of which contribute to plaque cap weakness. Additional benefits of melatonin relative to atherosclerosis is inhibition of adhesion molecules on the endothelial cell surface, limiting the invasion of monocytes into the arterial intima, and reducing the conversion of anti-inflammatory M2 macrophages to pro-inflammatory M1 macrophages. Given the high physiological and financial cost of cardiac and neural ischemic events, this information should be given high priority in the clinical setting.